(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This research aimed to develop in teachers’ competences in Economic and Financial Education (EEF), seeking that they train young students as citizens who make informed decisions regarding economic and financial issues impacting their life projects with quality and sustainability. The research made use of the methodology of the Investigation-Action. The information collected with documentary review, observation, field diary and teacher surveys, showed the absence of these skills. As a research product, teacher orientations are proposed for the articulation of this knowledge in making informed decisions, considering Guidelines of the Ministry of National Education in Colombia (MinEducación) on EEF, achieving impact through a Teacher Training Program to 13 schools in Atlántico, Colombia.